A Memory Advantage for Property. (1st April 2015) - DeScioli, Peter; Rosa, Nicole M.; Gutchess, Angela H.
People's access to resources depends on their status as the owner of particular items. To respect property, people need to remember who owns which objects. We test the hypothesis that people possess enhanced memory for ownership relations compared to unrelated objects. Participants viewed a sequence of 10 person-object pairs before completing a surprise associative memory test in which they matched each person with the previously paired object. We varied the description of the person-object pairs in the instructions. Across three experiments, participants showed better recall when the person was described as the owner of the object compared to being unrelated. Furthermore, memory for property was better than a physical relation (bumping), whereas it did not differ from mental relations (wanting and thinking). These patterns were observed both for memory of items (Experiments 1 and 2) and perceptual details (Experiment 3). We discuss implications for how people remember other people's property.